Positive electrode material, positive plate containing positive electrode material, preparation method of positive plate and lithium ion battery

By adding specific additives to the lithium iron phosphate positive electrode material, the stability and dispersion of the positive electrode slurry are improved, and the problem of insufficient flexibility and energy density of the positive electrode sheet is solved, and high coating surface density and compaction density are achieved.

CN119742367AInactive Publication Date: 2025-04-01HUANENG CLEAN ENERGY RES INST +1

Patent Information

Application Number
CN202411941594.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The lithium iron phosphate positive electrode sheet has problems with insufficient coating surface density and compaction density, which leads to insufficient flexibility and makes it difficult to achieve high energy density.

Method used

By adding specific additives to the positive electrode material, such as polyether, ethyl cellulose and small molecule alcohol having a weight average molecular weight of 80 to 1000, the stability and dispersion of the positive electrode slurry are improved, thereby preventing cracking during high-side density coating.

Benefits of technology

The flexibility and energy density of the positive electrode sheet are improved, and the high coating surface density and compaction density are achieved, which solves the problems of hardness, brittleness and cracking of the lithium iron phosphate positive electrode sheet.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742367A_ABST
    Figure CN119742367A_ABST
Patent Text Reader

Abstract

The invention relates to a positive electrode material, a positive plate containing the positive electrode material, a preparation method and a lithium ion battery. The positive electrode material comprises a positive electrode active material, conductive carbon black, a carbon nanotube, polyvinylidene fluoride and an additive, the additive is selected from one or more of polyether with the weight-average molecular weight of 80-1000 and containing-R1-O-R2-structural units, and R1 and R2 are independently selected from C1-6 alkylene; ethyl cellulose; the catalyst is selected from one or more of 2-amino-2-methyl-1-propanol, 2-amino-2-methyl-1, 3-propylene glycol, ethylene glycol, ethyl alcohol and tromethamine, and the micromolecular alcohol is selected from one or more of 2-amino-2-methyl-1-propanol, 2-amino-2-methyl-1, 3-propylene glycol, ethylene glycol, ethyl alcohol and tromethamine. According to the present invention, by adding the specific additive to the positive electrode material, the stability and the dispersibility of the positive electrode slurry can be improved, such that the current collector can be coated at the high surface density under the condition of no cracking so as to improve the flexibility and the energy density of the positive electrode plate containing the positive electrode material;
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium ion battery electrode materials, and in particular to positive electrode materials, positive electrode sheets containing the same and preparation methods, and lithium ion batteries. Background Art

[0002] In recent years, lithium-ion batteries have been used more and more widely in production and life, such as power batteries for new energy vehicles, electric bicycles, electric motorcycles, etc., or as energy storage systems for hydropower, wind power, and solar power stations. With the rapid development of the lithium battery industry, various industries have increasingly stringent requirements on it, especially energy density, cycle performance, and safety performance.

[0003] Lithium iron phosphate is a cathode material with low cost, long cycle life and high safety performance, which has attracted more and more attention. However, the current lithium iron phosphate cathode sheet has the problem of insufficient coating surface density and compaction density, which limits its application in new energy vehicles and other fields.

[0004] Lithium iron phosphate cathodes tend to become hard and brittle after being coated with PVDF binder, resulting in insufficient flexibility and difficulty in achieving high coating surface density and compaction density. Therefore, improving the flexibility of cathodes becomes the key to solving this problem.

[0005] At present, there are limited methods to improve the flexibility of lithium iron phosphate cathode sheets, and the cost and risk of developing new high energy density cathode materials are high. Therefore, finding a simple and effective method to improve the flexibility of lithium iron phosphate cathode sheets and achieve high coating surface density and compaction density is of great significance for improving the energy density of lithium batteries.

[0006] Therefore, it is necessary to propose a new method to solve the problem of insufficient flexibility of existing positive electrode sheets, thereby improving their coating surface density and compaction density and achieving the goal of high energy density. Summary of the invention

[0007] The main purpose of the present invention is to provide a positive electrode material, a positive electrode sheet containing the same and a preparation method, and a lithium ion battery, so as to solve the problems of insufficient flexibility and energy density of the positive electrode sheet in the prior art.

[0008] In order to achieve the above object, according to one aspect of the present disclosure, a positive electrode material for a lithium ion battery is provided, the positive electrode material comprising: a positive electrode active material, conductive carbon black, carbon nanotubes, polyvinylidene fluoride, and an additive, the additive being selected from one or more of the following: a polyether containing -R1-O-R2- structural units with a weight average molecular weight of 80 to 1000, wherein R1 and R2 are each independently selected from C 1-6Alkylene; ethyl cellulose; and a small molecule alcohol, the small molecule alcohol being selected from one or more of 2-amino-2-methyl-1-propanol, 2-amino-2-methyl-1,3-propanediol, ethylene glycol, ethanol and tromethamine.

[0009] Furthermore, in the positive electrode material of the present invention, the polyether is selected from one or more of polymethoxydimethyl ether, polyethylene oxide and polypropylene oxide.

[0010] Further, in the positive electrode material of the present invention, the ethyl cellulose has a weight average molecular weight of 400-1000 and an average degree of substitution of 2.3-2.6.

[0011] Further, in the positive electrode material of the present invention, the positive electrode material comprises: 90.0 to 97.0 parts by weight of a positive electrode active material, 0.3 to 4.0 parts by weight of conductive carbon black, 0.2 to 2.0 parts by weight of carbon nanotubes, 0.5 to 3.0 parts by weight of polyvinylidene fluoride, and 0.2 to 2.0 parts by weight of an additive.

[0012] Furthermore, in the positive electrode material of the present invention, the positive electrode active material is selected from one or more of lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide and lithium cobalt oxide.

[0013] According to another aspect of the present disclosure, a method for preparing a positive electrode sheet for a lithium-ion battery is provided, the method comprising the following steps: - Step S1: dissolving the above-mentioned positive electrode material of the present invention in an organic solvent to obtain a positive electrode slurry; - Step S2: coating the positive electrode slurry on a positive electrode current collector to obtain a positive electrode sheet.

[0014] Further, in the above method, in step S1, the solid content of the positive electrode slurry is in the range of 55wt% to 70wt%.

[0015] Furthermore, in the above method, in step S1, the viscosity of the positive electrode slurry is in the range of 3500 to 6000 mPa·s.

[0016] According to another aspect of the present disclosure, a positive electrode sheet for a lithium-ion battery is provided. The positive electrode sheet comprises the positive electrode material of the present invention or is prepared by the method of the present invention.

[0017] According to another aspect of the present disclosure, a lithium-ion battery is provided. The lithium-ion battery comprises: a positive electrode sheet, a negative electrode sheet, and a separator. The positive electrode sheet is the positive electrode sheet described above in the present invention.

[0018] In the positive electrode material, positive electrode sheet containing the same, preparation method, and lithium-ion battery of the present invention, by adding specific additives to the positive electrode material, the stability and dispersibility of the positive electrode slurry can be improved, so that the collector can be coated with a high surface density without cracking, thereby improving the flexibility and energy density of the positive electrode sheet containing the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The pictures show the test results of bending the positive electrode sheet prepared in Example 1 back and forth to wrap a 2 mm steel needle, where A, B, and C are bent once, twice, and three times respectively.

[0020] Figure 2 The pictures show the test results of bending the positive electrode sheet prepared in Example 2 back and forth to wrap a 2 mm steel needle, where A, B, and C are bent once, twice, and three times respectively. DETAILED DESCRIPTION

[0021] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present disclosure will be described in detail below in conjunction with the embodiments.

[0022] In view of the deficiencies in the prior art mentioned in the background technology, a specific embodiment of the present disclosure provides a positive electrode material for a lithium ion battery, the positive electrode material comprising: a positive electrode active material, conductive carbon black, carbon nanotubes, polyvinylidene fluoride, and an additive, wherein the additive is selected from one or more of the following: a polyether containing -R1-O-R2- structural units with a weight average molecular weight of 80 to 1000, wherein R1 and R2 are each independently selected from C 1-6 Alkylene; ethyl cellulose; and a small molecule alcohol, the small molecule alcohol being selected from one or more of 2-amino-2-methyl-1-propanol, 2-amino-2-methyl-1,3-propanediol, ethylene glycol, ethanol and tromethamine.

[0023] In the positive electrode material of the present invention, by adding specific additives to the positive electrode material, the stability and dispersibility of the positive electrode slurry can be improved, so that the current collector can be coated with a high surface density without cracking, thereby improving the flexibility and energy density of the positive electrode sheet containing the positive electrode material.

[0024] Polyethers and small molecule alcohols can undergo ion exchange reactions with polyvinylidene fluoride (PVDF) molecules, and ion exchange can improve the wettability and adhesion of the positive electrode slurry. In addition, ion exchange can also increase the bonding strength between the particles of the positive electrode slurry and improve the mechanical stability of the battery. Polyethers are also good solvents and dispersants, which can disperse positive electrode active materials such as lithium iron phosphate particles and other components in the positive electrode slurry to improve the dispersibility and stability of the battery. It can also promote chemical reactions on the surface of particles and enhance the structural stability of the positive electrode material. Polyethers and small molecule alcohols may also undergo chemical reactions such as addition reactions and esterification reactions with other components in the positive electrode slurry. These reactions can further improve the performance of the positive electrode slurry. For example, an addition reaction may occur between polyethers and PVDF to form a reinforced chemical cross-linked structure, thereby improving the electrical properties and stability of the positive electrode material.

[0025] A hydrogenation reaction may also occur between the small molecule alcohol additive and PVDF, inducing a cross-linking reaction in PVDF during high temperature baking after coating, forming a cross-linking network, improving the cohesion and peeling force of the positive electrode, thereby solving the problem of brittleness of the electrode caused by PVDF as a binder and cracking due to excessive coating. The hydrogenation reaction refers to the reaction process in which the hydrogen atoms in the alcohol molecule are pulled out to form a double bond structure when the alcohol reacts with PVDF.

[0026] Specifically, the hydrogen atoms in the alcohol molecules can undergo nucleophilic addition reactions with the fluorinated groups in PVDF to form an ethoxy group, while breaking to form a hydrogen ion. This free hydrogen ion can be acquired by the adjacent carbonyl group (a group containing a carbon-oxygen double bond) to form a CC bond, while releasing an oxygen atom. The chemical formula for this reaction is as follows: ROH+PVDF→RO-PVDF+HX, where ROH represents an alcohol molecule, PVDF represents polyvinylidene fluoride, RO-PVDF represents an alcohol-polymer copolymer, and HX represents a carbon-carbon single bond formed by a hydrogen ion and an adjacent carbonyl group. Therefore, the hydrogen extraction reaction can change the chemical structure of PVDF, thereby improving the wettability and adhesion between the positive electrode slurry and the current collector, and preventing the cracking of the positive electrode sheet during high surface density coating.

[0027] Polyether can also improve the problem of positive electrode cracking by reducing the semi-crystallinity of PVDF. Generally speaking, PVDF has two sequences, polar and non-polar, and the semi-crystalline structure is produced by the interaction between the polar and non-polar sequences of PVDF molecules. Additives can change the structural distribution of PVDF sequences, forming fewer and shorter crystalline structures, thereby reducing the degree of semi-crystallinity of PVDF. This can make PVDF more plastic and soft, reducing the risk of cracking of the positive electrode.

[0028] In addition, polyether also has a certain effect on the solid content of the positive electrode slurry. Adding a suitable polyether additive can make PVDF and the positive electrode active material more compatible, making the solid content higher, thereby improving the energy density and capacity of the positive electrode sheet. During the coating process, due to the increase in solid content, the pole piece evaporates less solvent during the drying process, and the positive electrode sheet has less internal stress due to solvent evaporation, thereby preventing the problem of cracking of the pole piece during high surface density coating.

[0029] Ethylcellulose is the ethyl ether of cellulose, and thus ethylcellulose functions in a manner similar to polyethers.

[0030] The weight average molecular weight of the polyether can be, for example, 80, 90, 100, 130, 160, 190, 200, 230, 260, 290, 300, 330, 360, 390, 400, 430, 460, 490, 500, 530, 560, 590, 600, 630, 660, 690, 700, 730, 760, 790, 800, 830, 860, 890, 900 or 1000. The selection of the weight average molecular weight of the polyether directly affects the stability and dispersibility of the positive electrode slurry. The polyether having a weight average molecular weight within this range can effectively improve the stability and dispersibility of the positive electrode slurry, can prevent cracking and is suitable for high energy density and high power density design of the battery.

[0031] R1 and R2 may each independently be, for example, a methylene group, an ethylene group, a propylene group, a butylene group, a pentylene group or a hexylene group.

[0032] In some embodiments of the present invention, in the cathode material of the present invention, the polyether is selected from one or more of polymethoxy dimethyl ether, polyethylene oxide and polypropylene oxide. Preferably, the polyether can be selected from one or more of polymethoxy dimethyl ether, polyethylene oxide and polypropylene oxide with a weight average molecular weight of 300-600.

[0033] In some embodiments of the present invention, in the positive electrode material of the present invention, ethyl cellulose has a weight average molecular weight of 400-1000 and an average degree of substitution of 2.3-2.6. Preferably, ethyl cellulose may have a weight average molecular weight of 500-800 and an average degree of substitution of 2.4-2.6. For example, ethyl cellulose may have a weight average molecular weight of 500, 600, 700 or 800 and an average degree of substitution of 2.4, 2.5 or 2.6.

[0034] In some embodiments of the present invention, in the positive electrode material of the present invention, the positive electrode material comprises: 90.0 to 97.0 parts by weight of positive electrode active material, 0.3 to 4.0 parts by weight of conductive carbon black, 0.2 to 2.0 parts by weight of carbon nanotubes, 0.5 to 3.0 parts by weight of polyvinylidene fluoride, and 0.2 to 2.0 parts by weight of additives. By using the additives in a ratio within this range, the rheological properties of the positive electrode slurry can be more effectively improved, the viscosity of the positive electrode slurry can be reduced, and the uniformity and compactness of the coating can be improved while preventing cracking, thereby reducing the production cost while ensuring the battery performance, and being suitable for large-scale industrial production.

[0035] Preferably, the positive electrode material may include: 92.0-95.0 parts by weight of a positive electrode active material, 2.0-3.0 parts by weight of conductive carbon black, 0.5-2.0 parts by weight of carbon nanotubes, 1.5-3.0 parts by weight of polyvinylidene fluoride, and 0.2-1.0 parts by weight of an additive. For example, the additive may be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2.0 parts by weight.

[0036] In some embodiments of the present invention, in the positive electrode material of the present invention, the positive electrode active material is selected from one or more of lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide and lithium cobalt oxide. The present invention has no particular limitation on the positive electrode active material, and the positive electrode active materials given above are only given as examples, and those skilled in the art can select a suitable positive electrode active material according to actual needs.

[0037] According to another embodiment of the present invention, a method for preparing a positive electrode sheet for a lithium-ion battery is provided, the method comprising the following steps: - Step S1: dissolving the above-mentioned positive electrode material of the present invention in an organic solvent to obtain a positive electrode slurry; - Step S2: coating the positive electrode slurry on a positive electrode current collector to obtain a positive electrode sheet.

[0038] In the preparation method of the positive electrode sheet for a lithium-ion battery of the present invention, by adding specific additives to the positive electrode material, the stability and dispersibility of the positive electrode slurry can be improved, so that the current collector can be coated with a high surface density without cracking, thereby improving the flexibility and energy density of the positive electrode sheet containing the positive electrode material.

[0039] In some embodiments of the present invention, in the above method, in step S1, the solid content of the positive electrode slurry can be in the range of 55wt% to 70wt%. For example, the solid content of the positive electrode slurry can be 55wt%, 56wt%, 57wt%, 58wt%, 59wt%, 60wt%, 61wt%, 62wt%, 63wt%, 64wt%, 65wt%, 66wt%, 67wt%, 68wt%, 69wt% or 70wt%. By using a positive electrode slurry with a solid content within this range, not only can the energy density and capacity of the positive electrode sheet be more effectively improved, but also the solvent volatilization of the positive electrode sheet during the drying process can be reduced, and the internal stress of the positive electrode sheet due to the volatilization of the solvent is reduced, thereby better preventing the problem of cracking of the electrode sheet during high surface density coating.

[0040] In some embodiments of the present invention, in the above method, in step S1, the viscosity of the positive electrode slurry is in the range of 3500 to 6000 mPa·s. This viscosity range can better ensure the stability and controllability of the positive electrode slurry during the coating process, thereby more effectively avoiding bubbles and cracks during the coating process, further improving the consistency and reliability of the battery, and is particularly suitable for battery manufacturing processes that require high-precision coating.

[0041] Preferably, in step S2, the positive electrode slurry may be prepared at a concentration of 200 to 320 g / m 2 The surface density can be, for example, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 310 or 320 g / m 2 .

[0042] The present invention has no particular restrictions on the positive electrode current collector, and those skilled in the art can select a suitable positive electrode current collector according to actual needs. Preferably, the positive electrode current collector can be, for example, carbon-coated aluminum foil. This can further enhance the binding force between the positive electrode active material and the positive electrode current collector and the conductivity of the positive electrode sheet.

[0043] According to another embodiment of the present invention, a positive electrode sheet for a lithium-ion battery is provided. The positive electrode sheet comprises the positive electrode material of the present invention or is prepared by the method of the present invention.

[0044] In positive electrode sheets for lithium-ion batteries, the stability and dispersibility of the positive electrode slurry can be improved by adding specific additives to the positive electrode material, so that the current collector can be coated at a high surface density without cracking, thereby improving the flexibility and energy density of the positive electrode sheet containing the positive electrode material.

[0045] According to another embodiment of the present invention, a lithium-ion battery is provided. The lithium-ion battery comprises: a positive electrode sheet, a negative electrode sheet, and a separator. The positive electrode sheet is the positive electrode sheet described above in the present invention.

[0046] In lithium-ion batteries, by adding specific additives to the positive electrode material, the stability and dispersibility of the positive electrode slurry can be improved, allowing the current collector to be coated at a high surface density without cracking, thereby improving the flexibility and energy density of the positive electrode sheet containing the positive electrode material.

[0047] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0048] Example

[0049] Example 1

[0050] (1) Preparation of positive electrode

[0051] 1000.00g lithium iron phosphate (LFP), 32.61g conductive carbon black (SP), 5.44g carbon nanotubes (CNT), 21.74g PVDF and 5.44g polyethylene oxide (weight average molecular weight 400g / mol) additives were added to 1100ml N-methylpyrrolidone, wherein the mass ratio of LFP:SP:CNT:PVDF:additives was 92.0:3.0:0.5:2.0:0.5, and the positive electrode slurry was obtained after mixing and stirring. The positive electrode slurry was evenly coated on the positive electrode current collector carbon-coated aluminum foil, and the coating surface density was 260g / m 2 After drying, rolling and die-cutting, the positive electrode sheet is obtained.

[0052] After the obtained positive electrode sheet was bent back and forth to wrap the 2mm steel needle three times, the positive electrode sheet did not fall off and was not transparent. Figure 1 The pictures show the flexibility test results of the positive electrode sheet after bending, A, B, and C are bent once, twice, and three times respectively.

[0053] (2) Preparation of negative electrode sheet

[0054] 900g of artificial graphite, 30g of SP, 40g of sodium carboxymethyl cellulose (CMC), and 30g of styrene-butadiene rubber (SBR) were added to 1000ml of water, wherein the mass ratio of artificial graphite: SP: CMC: SBR was 90.0: 3.0: 4.0: 3.0, and the negative electrode slurry was obtained after being mixed evenly. The negative electrode slurry was evenly coated on the negative electrode current collector copper foil, and the coating surface density was adjusted according to the positive and negative electrode N / P ratio, and then dried, rolled, and die-cut to obtain a negative electrode sheet.

[0055] (3) Battery assembly

[0056] A polyethylene film containing ceramic and alumina coating is used as a separator, and the negative electrode sheet, separator, and positive electrode sheet are stacked in sequence, with the separator being placed between the positive electrode sheet and the negative electrode sheet for assembly to prepare a lithium-ion battery. The moisture content of the positive electrode sheet, the negative electrode sheet, and the separator is required to be below 300ppm, 150ppm, and 500ppm, respectively, before assembly.

[0057] (4) Battery formation, capacity division and capacity determination

[0058] After the battery is assembled, it is injected with liquid and then aged at room temperature for 24 hours to ensure that the electrolyte completely soaks the entire battery cell. After aging, it is formed, and the formation is respectively charged at 0.02C constant current for 3 hours or charged to 3.1V, then charged at 0.1C constant current for 1 hour, and finally charged at 0.2C constant current for 2 hours or charged to 3.45V. After the formation is completed, the battery is aged at 45℃ for 24 hours and 25℃ for 12 hours, and then divided and fixed. The battery production is completed.

[0059] Example 2

[0060] The difference between Example 2 and Example 1 is only the preparation process of the positive electrode sheet: 1000g LFP, 23.66g SP, 19.35g CNT, 32.26g PVDF, and 6.45g 2-amino-2-methyl-1-propanol additive are added to 1100ml N-methylpyrrolidone, wherein the mass ratio of LFP:SP:CNT:PVDF:additive is 93.0:2.2:1.8:3.0:0.6, and the positive electrode slurry is obtained after mixing and stirring evenly. The positive electrode slurry is evenly coated on the positive electrode current collector carbon-coated aluminum foil, and the coating surface density is 270g / m 2 After drying, rolling and die-cutting, the positive electrode sheet is obtained.

[0061] After the obtained positive electrode sheet was bent back and forth to wrap the 2mm steel needle three times, the positive electrode sheet did not fall off and was not transparent. Figure 2 The pictures show the flexibility test results of the positive electrode sheet after bending, A, B, and C are bent once, twice, and three times respectively.

[0062] Example 3

[0063] The difference between Example 3 and Example 1 is only in the preparation process of the positive electrode sheet: 1000g LFP, 32.54g SP, 21.70g CNT, 27.12g PVDF and 3.25g polyethylene oxide (weight average molecular weight 400g / mol) additives are added to 1100ml N-methylpyrrolidone, wherein the mass ratio of LFP:SP:CNT:PVDF: additive is 92.2:3.0:2.0:2.5:0.3, and then 4.34g (0.4wt.%) of 2-amino-2-methyl-1-propanol is additionally added thereto, and the mixture is mixed and stirred to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on the positive electrode current collector carbon-coated aluminum foil, and the coating surface density is 280g / m 2 After drying, rolling and die-cutting, the positive electrode sheet is obtained.

[0064] After the obtained positive electrode sheet was bent back and forth three times to wrap a 2mm steel needle, the positive electrode sheet did not fall off and was not light-transmissive.

[0065] Example 4

[0066] The difference between Example 4 and Example 1 is only in the preparation process of the positive electrode sheet: 1000g LFP, 31.75g ​​SP, 6.35g CNT, and 20.10g PVDF are added to 1100ml N-methylpyrrolidone, wherein the mass ratio of LFP:SP:CNT:PVDF is 94.5:3.0:0.6:1.9, and then 3.17g (0.3wt.%) of tromethamine is added thereto, and the mixture is mixed and stirred to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on the positive electrode current collector carbon-coated aluminum foil, and the coating surface density is 270g / m 2 After drying, rolling and die-cutting, the positive electrode sheet is obtained.

[0067] After the obtained positive electrode sheet was bent back and forth three times to wrap a 2mm steel needle, the positive electrode sheet did not fall off and was not light-transmissive.

[0068] Example 5

[0069] The difference between Example 5 and Example 1 is only the preparation process of the positive electrode sheet: 1000g LFP, 32.43g SP, 6.49g CNT, 21.62g PVDF and 9.73g ethyl cellulose (weight average molecular weight of 800g / mol, average degree of substitution of 2.5) are added to 1100ml N-methylpyrrolidone, wherein the mass ratio of LFP:SP:CNT:PVDF:ethyl cellulose is 92.5:3.0:0.6:2.0:0.9, and the positive electrode slurry is obtained after mixing and stirring evenly. The positive electrode slurry is evenly coated on the positive electrode current collector carbon-coated aluminum foil, and the coating surface density is 260g / m 2After drying, rolling and die-cutting, the positive electrode sheet is obtained.

[0070] After the obtained positive electrode sheet was bent back and forth three times to wrap a 2mm steel needle, the positive electrode sheet did not fall off and was not light-transmissive.

[0071] Comparative Example 1

[0072] The only difference between Comparative Example 1 and Example 1 is that no polyethylene oxide additive is added during the preparation of the positive electrode sheet.

[0073] After the obtained positive electrode sheet was bent back and forth three times to wrap a 2 mm steel needle, the positive electrode sheet was severely detached.

[0074] Comparative Example 2

[0075] The only difference between Comparative Example 2 and Example 2 is that no 2-amino-2-methyl-1-propanol additive is added during the preparation of the positive electrode sheet.

[0076] After the obtained positive electrode sheet was bent back and forth three times to wrap a 2 mm steel needle, the positive electrode sheet was severely detached.

[0077] Comparative Example 3

[0078] The difference between Comparative Example 3 and Example 3 is that polyethylene oxide and 2-amino-2-methyl-1-propanol additives are not added during the preparation of the positive electrode sheet.

[0079] After the obtained positive electrode sheet was bent back and forth three times to wrap a 2 mm steel needle, the positive electrode sheet was severely detached.

[0080] Comparative Example 4

[0081] The only difference between Comparative Example 4 and Example 4 is that tromethamine is not added during the preparation of the positive electrode sheet.

[0082] After the obtained positive electrode sheet was bent back and forth three times to wrap a 2 mm steel needle, the positive electrode sheet was severely detached.

[0083] Comparative Example 5

[0084] The only difference between Comparative Example 5 and Example 5 is that ethyl cellulose is not added during the preparation of the positive electrode sheet.

[0085] After the obtained positive electrode sheet was bent back and forth three times to wrap a 2 mm steel needle, the positive electrode sheet was severely detached.

[0086] It can be seen from the above experimental results that the above embodiments of the present invention achieve the following technical effects:

[0087] Compared with comparative examples 1-5, the positive electrode sheets prepared in examples 1-5 of the present invention do not drop and are not light-transmissive. Therefore, in the positive electrode sheet of the present invention, by adding a specific additive to the positive electrode material, the stability and dispersibility of the positive electrode slurry can be improved, so that the current collector can be coated at a high surface density without cracking, thereby improving the flexibility and energy density of the positive electrode sheet containing the positive electrode material.

[0088] The above description only relates to specific embodiments of the present disclosure and is not intended to limit the present disclosure. For those skilled in the art, the present disclosure may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present disclosure shall be included in the protection scope of the present disclosure.

Claims

1. A positive electrode material for a lithium ion battery, characterized in that: The positive electrode material comprises: Positive electrode active material, Conductive carbon black, Carbon nanotubes, Polyvinylidene fluoride, and Additives, the additives are selected from one or more of the following: A polyether containing -R1-O-R2- structural units with a weight average molecular weight of 80 to 1000, wherein R1 and R2 are each independently selected from C 1-6 Alkylene, Ethyl cellulose, and The small molecule alcohol is selected from one or more of 2-amino-2-methyl-1-propanol, 2-amino-2-methyl-1,3-propanediol, ethylene glycol, ethanol and tromethamine.

2. The positive electrode material according to claim 1, characterized in that The polyether is selected from one or more of polymethoxydimethyl ether, polyethylene oxide and polypropylene oxide.

3. The positive electrode material according to claim 1, characterized in that The ethyl cellulose has a weight average molecular weight of 400-1000 and an average degree of substitution of 2.3-2.

6.

4. The positive electrode material according to any one of claims 1 to 3, characterized in that The positive electrode material comprises: 90.0 to 97.0 parts by weight of the positive electrode active material, 0.3 to 4.0 parts by weight of the conductive carbon black, 0.2 to 2.0 parts by weight of the carbon nanotubes, 0.5 to 3.0 parts by weight of polyvinylidene fluoride, and 0.2 to 2.0 parts by weight of the additive.

5. The positive electrode material according to any one of claims 1 to 3, characterized in that The positive electrode active material is selected from one or more of lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide and lithium cobalt oxide.

6. A method for preparing a positive electrode sheet for a lithium ion battery, characterized in that: The following steps are involved: - Step S1: dissolving the positive electrode material according to any one of claims 1 to 5 in an organic solvent to obtain a positive electrode slurry; - Step S2: coating the positive electrode slurry on a positive electrode current collector to obtain a positive electrode sheet.

7. The method according to claim 6, characterized in that In the step S1, the solid content of the positive electrode slurry is in the range of 55 wt% to 70 wt%.

8. The method according to claim 6 or 7, characterized in that: In the step S1, the viscosity of the positive electrode slurry is in the range of 3500 to 6000 mPa·s.

9. A positive electrode sheet for a lithium ion battery, characterized in that: The positive electrode sheet comprises the positive electrode material according to any one of claims 1 to 5 or is prepared by the method according to any one of claims 6 to 8.

10. A lithium ion battery comprising: Positive electrode, The negative electrode, and Diaphragm, It is characterized in that The positive electrode sheet is the positive electrode sheet described in claim 9.

Citation Information

Patent Citations

  • Nickel lithium manganate-based positive electrode material of lithium ion battery and preparation method thereof

    CN105355903A

  • Ethyl cellulose as a dispersant for lithium ion battery cathode production

    CN112368859A

  • Additive for positive electrode of lithium ion battery, positive electrode slurry using additive and preparation method of positive electrode slurry

    CN113410462A

  • Thick positive electrode piece, preparation method thereof and lithium ion battery

    CN113611823A

  • High-energy-density battery electrode and low-carbon preparation method and application thereof

    CN113629252A

Cited By

  • Positive electrode additive, preparation method thereof, battery containing positive electrode additive and electric device

    CN120757772A